Lipidomic and Instrumental Evaluation of a Melatonin-Based In & Out Strategy Versus Topical Treatment in Skin Aging: A Randomized Prospective Trial - Francesca Colombo; Stefano Alfano; Massimo Milani (Metabolites)
This study aimed to evaluate the efficacy of a novel “In & Out” strategy, combining topical and oral melatonin supplementation, in managing skin aging compared to topical treatment alone. A randomized, prospective study was conducted on 39 healthy females aged 55–69 years. Participants were divided into two groups: one received both the topical formula and oral melatonin supplementation (Group A), while the other received a topical melatonin-based formula (Group B). Clinical evaluations included lipidomic analysis, skin moisturization, and wrinkle depth analysis at baseline and after 84 days. The addition of oral melatonin supplementation to the topical regimen led to improvements in the skin’s lipid profile and moisturization levels. These findings suggest that combining topical and oral melatonin may provide a more comprehensive approach to managing skin aging by addressing both local and systemic factors. Background/Objectives: With age, the endogenous antioxidant capacity of the skin decreases, including melatonin (Mel) synthesis. Skin aging is also associated with alterations in epidermal lipids, particularly a reduction in triglycerides and ceramides, which are essential for maintaining skin structure and hydration. The administration of exogenous melatonin could, therefore, be an effective anti-aging strategy. While some data suggest that melatonin may positively influence the lipid profile, specific data on its effects on skin aging are lacking. This study aimed to evaluate the anti-aging effects of an “In & Out” regimen consisting of a Mel-based cream and dietary supplement in comparison with topical treatment alone, focusing on clinical and lipidomic changes involved in skin homeostasis. Results: A statistically significant variation was observed in both groups compared to baseline (T0) in terms of moisturization (+23.6% in Group A, +18.3% in Group B) and wrinkle depth (−18.5% in Group A, −9.4% in Group B, p < 0.05). Both groups showed improvements in the lipid content of the skin, which typically decreases with age. The “In & Out” strategy resulted in a statistically significant increase in triacylglycerols and ceramides, key lipids that exhibit water-holding properties. Conclusions: The “In & Out” melatonin-based regimen demonstrated greater efficacy in clinical improvement and positive lipid profile modifications compared to topical treatment alone, highlighting its potential as a comprehensive anti-aging strategy.